1996
DOI: 10.1128/jcm.34.1.144-148.1996
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic and phenotypic characterization of Escherichia coli isolates from dogs manifesting attaching and effacing lesions

Abstract: Thirteen Escherichia coli isolates from dogs manifesting attaching and effacing lesions were characterized genetically with respect to the presence of the following virulence determinants associated with human enteropathogenic E. coli (EPEC): eaeA, encoding the outer membrane protein intimin; eaeB, which is necessary for inducing signal transduction; bfpA, encoding the bundle-forming pilus; and the EAF (stands for EPEC adherence factor) plasmid. These isolates were also analyzed phenotypically with respect to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(28 citation statements)
references
References 42 publications
0
27
0
1
Order By: Relevance
“…When putative canine strains of EPEC (Drolet et al, 1994a) were examined in vitro, it was found that all of nine eae-positive isolates adhered to piglet ileum and produced AE lesions, but only one adhered and formed FAS-positive lesions on HEp-2 cells (Beaudry et al, 1996). Putative AEEC isolated from dogs and cats encompassed a range of serogroups (Holland et al, 1999a).…”
Section: Other Mammalsmentioning
confidence: 99%
“…When putative canine strains of EPEC (Drolet et al, 1994a) were examined in vitro, it was found that all of nine eae-positive isolates adhered to piglet ileum and produced AE lesions, but only one adhered and formed FAS-positive lesions on HEp-2 cells (Beaudry et al, 1996). Putative AEEC isolated from dogs and cats encompassed a range of serogroups (Holland et al, 1999a).…”
Section: Other Mammalsmentioning
confidence: 99%
“…Dog EPEC (DEPEC) strain 4221 possesses sequences homologous to eae and espB [15]. When tested with HEp-2 cells, strain 4221 showed a localized adherence and is positive in the £uorescence actin staining test [15]. These ¢ndings indicate that DEPEC strain 4221 is more similar to human EPEC isolates than to AEEC isolates obtained from pigs [16], rabbits [17] or calves [13].…”
Section: Introductionmentioning
confidence: 92%
“…E. coli strain 4221 was isolated from the intestinal contents of a dog with diarrhea and demonstrating typical AE lesions [15]. This strain was stored on Dorset medium at 4³C and grown on blood agar or in trypticase soy broth (Difco Laboratories, Detroit Mich) at 37³C.…”
Section: Bacterial Strains and Plasmidsmentioning
confidence: 99%
See 2 more Smart Citations